Pencegahan Kerugian Negara Melalui Penguatan Regulasi Hubungan Kerja Pemeriksa Eksternal Dengan Pengawas Internal: Preventing State Losses by Strengthening the Regulatory Framework Governing the Working Relationship between External Auditors and Internal Supervisors - Priyatno, Agus Adi (SHARE Journal, 2025)
Preventing state financial losses is a crucial component of strengthening the state’s inspection and oversight system. However, the regulatory framework on the relationship between the Audit Board (BPK) as an external auditor and the Government Internal Supervisory Apparatus (APIP) as an internal supervisor needs to be strengthened. This study examines the importance of preventing state losses by reinforcing regulations governing collaboration between BPK and APIP, offering scholarly insights to enhance the effectiveness of the financial oversight system. A normative juridical method, employing statutory and conceptual approaches, was used to examine the authority, functions, and institutional relationships of both entities. The study reveals that existing regulations do not suggest synergy, integration, or collaboration, leading to an oversight approach that is predominantly retrospective and repressive. The study recommends regulatory refinement grounded in five core principles: governance and independence, synergy and role optimization, technical standards and integrated data, procedural regulation, and sustainability.